Seroprevalence of Herpes Simplex virus types 1 and 2 and their association with CD4 count among HIV-positive patients - Irna Sufiawati; Sunardhi Widyaputra; Tony S. Djajakusumah (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Herpes simplex virus (HSV) is a common cause of viral opportunistic infections among HIV-positive patients. Frequent, more severe and prolonged episodes of recurrent HSV infection can be a source of significant morbidity and mortality among HIV-positive patients with advanced immunosuppression, reflected by low CD4 count. However, conflicting results have also been reported. Purpose: The aim of this study was to investigate the seroprevalence of HSV type 1 (HSV-1) and type 2 (HSV-2) in HIV-positive patients compare with the rate in HIV-negative patients, and to evaluate their association with CD4 count. Methods: A cross sectional study was conducted among 145 subjects consisting of 80 HIV-positive and 65 HIV-negative patients attending the top referral hospital in Bandung, West Java, Indonesia. The serum obtained was assayed for the presence of HSV-1 and HSV-2 IgG antibodies using ELISA kits. Data were analyzed using a Chi-square test, t-tests and analysis of variance (ANOVA). Results: There were no significant differences in HSV-1 seroprevalence between HIV-positive patients (71%) and HIV-negative patients (66%). HSV-2 seroprevalence was significantly higher in HIV-positive patients (30%) than HIV-negative patients (5%). The titers of HSV-1 IgG antibodies in HIV-positive patients (mean 24.63 ± 19.06 IDU) were significantly lower than those of HIV-negative patients (mean 44.62 ± 33.22 IDU). In contrast, HSV-2 IgG antibody titers in HIV-positive patients (mean 13.31 ± 20.28 IDU) were significantly higher than HIV-negative patients (mean 4.42 ± 10.99 IDU). There was no significant correlation between HSV-1 and HSV-2 seropositivity and CD4 count among HIV-positive patients. However, most of HSV-2 seropositive patients had CD4 count < 200 cells/mm3. Conclusion: Seroprevalence of HSV-1 and HSV-2 among HIV-positive patients was high with no correlation with CD4 count.Latar belakang: Herpes simplex virus (HSV) adalah penyebab infeksi virus oportunistik yang paling umum pada pasien HIVpositif. Infeksi HSV rekuren yang sering terjadi, lebih berat, dan episode yang berkepanjangan dapat menjadi penyebab morbiditas dan mortalitas yang signifikan pada pasien HIV-positif dengan imunosupresi lanjut, ditandai dengan jumlah CD4 yang rendah. Namun, hasil yang bertentangan juga telah dilaporkan. Tujuan: Penelitian ini bertujuan untuk mengetahui seroprevalensi HSV tipe 1 (HSV-1) dan tipe 2 (HSV-2) pada pasien HIV-positif dibandingkan dengan pasien HIV-negatif, dan untuk mengevaluasi hubungannya dengan jumlah CD4. Metode: Penelitian potong lintang ini dilakukan pada 145 subjek yang terdiri dari 80 pasien HIV-positif dan 65 pasien HIV-negatif yang berkunjung ke rumah sakit pusat rujukan di Bandung, Jawa Barat, Indonesia. Antibodi IgG HSV-1 dan HSV-2 di dalam serum diperiksa dengan menggunakan ELISA. Data dianalisis dengan uji Chi-square, t-test dan ANOVA, nilai p < 0.05 dianggap signifikan secara statistik. Hasil: Seroprevalensi antibodi IgG HSV-1 pada pasien HIV-positif (71%) tidak berbeda secara signifikan dengan pasien HIV-negatif (66%). Namun, seroprevalensi HSV-2 secara signifikan lebih tinggi pada pasien HIV-positif (30%) dibandingkan dengan pasien HIV-negatif (5%). Titer antibodi IgG HSV-1 pada pasien HIV-positif (mean 24.63 ± 19.06 IDU) secara signifikan lebih rendah dibandingkan pasien HV-negatif (mean 44.62 ± 33.22 IDU). Sedangkan, titer antibodi IgG HSV-2 pada pasien HIV-positif (mean 13.31 ± 20.28 IDU) secara signifikan lebih tinggi dibandingkan pasien HIV-negatif (mean 4.42 ± 10.99 IDU). Tidak ada hubungan yang signifikan antara seropositivitas HSV-1 dan -2 dengan jumlah CD4. Namun, sebagian besar pasien seropositif HSV-2 memiliki jumlah CD4 < 200 sel/mm3. Kesimpulan: Seroprevalensi HSV-1 dan HSV-2 pada pasien HIV-positif adalah tinggi, tetapi tidak berkorelasi dengan jumlah CD4.